Fruit Industry 2022
DOI: 10.5772/intechopen.102361
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Composition of Japanese Quince (Chaenomeles japonica) and Its Promising Value for Food, Cosmetic, and Pharmaceutical Industries

Abstract: Japanese quince (Chaenomeles japonica) is one of the most underutilized plant species that have high nutrient value and a positive impact on human health. Due to the high content of bio-compounds, such as phenols, vitamin C, triterpenes, fibers, essential amino acids, and microelements, the fruits, leaves, and seeds are excellent raw materials for functional food production. In addition, their biochemical composition and anti-inflammatory, anticancer, and antibacterial properties expanded their uses in the pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Other researchers [ 41 ] assessed the impact of adding freeze-dried and ground Japanese quince ( Chaenomeles japonica ) fruits on the properties of cookies. Japanese quince is a source of polyphenolic compounds, such as catechin, epicatechin, chlorogenic acid, procyanidin B1, and procyanidin B2, which, together with the biologically active form of vitamin C, determine the antioxidant potential of the fruit [ 42 ]. The 0.5% addition to the cookies resulted in a two-fold increase in antiradical activity against DPPH, while the 9.5% addition resulted in a 3.5-fold improvement over the control.…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…Other researchers [ 41 ] assessed the impact of adding freeze-dried and ground Japanese quince ( Chaenomeles japonica ) fruits on the properties of cookies. Japanese quince is a source of polyphenolic compounds, such as catechin, epicatechin, chlorogenic acid, procyanidin B1, and procyanidin B2, which, together with the biologically active form of vitamin C, determine the antioxidant potential of the fruit [ 42 ]. The 0.5% addition to the cookies resulted in a two-fold increase in antiradical activity against DPPH, while the 9.5% addition resulted in a 3.5-fold improvement over the control.…”
Section: Changes In Chemical Composition and Antioxidant Activitymentioning
confidence: 99%
“…However, due to their characteristics, such as firmness and sourness, they are not suitable for fresh consumption, so they are mainly used to produce juices, syrups, alcoholic and non-alcoholic beverages, etc. 17 . They contain antioxidants like B and C vitamins, epicatechin, iron, copper, zinc, kaempferol, quercetin, etc.…”
mentioning
confidence: 99%
“…However, the differences in their amounts reported in the literature are significant, depending on the variety, growing conditions, extraction method, and solvent used. According to research on the extraction of C. japonica phenolics, the most effective extractants among the nine tested were 50% ethanol, 100% methanol, and 50-70% acetone [61].…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…The analysis is complicated by the fact that sometimes extracts were prepared from whole fruits after removal of the seed core, probably due to the smaller size of the fruits, and then freeze-dried, in which case the results of all measurements were expressed on a dry weight basis, while other researchers used extracts from fresh pulp. Urbanavičiūtė et al [61] analyzed the total phenolic content in C. japonica extracts and found that it ranged from 4523 to 6785 mg/100 g dm. Significant differences in the obtained values resulted from specific combinations of parameters (i.e., type of solvent, time, power and temperature of ultrasonic extraction).…”
Section: Phenolic Compoundsmentioning
confidence: 99%